Application AVATAR (Accounting Virtual Report) on PT Pelindo Terminal Petikemas - Monika Handayani; Fitria Fitria; Akhmad Faizal Rahman (International Journal of Management Research and Economics, 2024)
This research discusses the application of asset maintenance at PT Pelindo Terminal Petikemas. This research aims to determine the asset maintenance system at PT Pelindo Terminal Petikemas, as well as to create a web-based asset maintenance application program at PT Pelindo Terminal Petikemas. The theoretical framework of this research involves information system analysis, by examining the information needed by management, related functions, documents used, as well as document flowcharts. MySql is used as a database, with the PHP programming language. The research results show that the recording process at PT Pelindo Terminal Petikemas has been computerized but still uses Microsoft Excel. The weakness of this method is that it is difficult to look back at archived data for the previous year because you need to search for the file first and there is a risk of losing the file. Therefore, the application called AVATAR (Accounting Virtual Report) in this research is expected to help produce asset maintenance reports more effectively and efficiently, thus providing benefits for the company.